2018
DOI: 10.1186/s40645-018-0221-6
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake early warning: what does “seconds before a strong hit” mean?

Abstract: An earthquake early warning (EEW) system is designed to detect an event, determine its parameters (hypocenter, magnitude, and origin time), and issue an alert to sites/areas where necessary actions should be taken before destructive seismic energy arrivals. At present, large-scale EEW systems are operational in several countries around the world. The most extensive nationwide EEW system has been operating in Japan since 2007, and was able to issue alerts broadly when the moment magnitude (Mw) 9 Tohoku-Oki eart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…This desire is shared worldwide, including by over 200 participants (organizations) of a survey that assessed the factors influencing organizational acceptance and use of EEW systems in California (Goltz, 2002). Tajima and Hayashida (2018) conclude that some types of information that can be used to determine the most appropriate actions to take, such as the arrival time, should be also be considered. In particular, the survey respondents in the study by Goltz (2002) indicated that mitigation actions such as "moving away from falling objects" or "shutting off gas lines" are the most appropriate measures in a short warning time (10 s), while "evacuating to an outside area" or "shutting down hazardous materials" are more effective options when a longer warning time is available (50 s).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This desire is shared worldwide, including by over 200 participants (organizations) of a survey that assessed the factors influencing organizational acceptance and use of EEW systems in California (Goltz, 2002). Tajima and Hayashida (2018) conclude that some types of information that can be used to determine the most appropriate actions to take, such as the arrival time, should be also be considered. In particular, the survey respondents in the study by Goltz (2002) indicated that mitigation actions such as "moving away from falling objects" or "shutting off gas lines" are the most appropriate measures in a short warning time (10 s), while "evacuating to an outside area" or "shutting down hazardous materials" are more effective options when a longer warning time is available (50 s).…”
Section: Discussionmentioning
confidence: 99%
“…Strong organizational links with representatives of official bodies and first responders are also required to make EEW a successful tool for enhancing business continuity in critical infrastructure such as energy, utilities, food supply, communications, and banking (Gasparini et al, 2011). As indicated by Tajima and Hayashida (2018), EEW systems are only effective if the resilience, strength, and operations of the system are ensured before ground shaking occurs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations